2013
DOI: 10.3109/0886022x.2013.823830
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in peripheral arterial surgery patients: a cohort study

Abstract: Purpose: The aim of the study was to evaluate the prevalence of acute kidney injury (AKI) in a cohort of surgically treated patients with peripheral artery disease (PAD) and its association with the short-term and long-term outcome. Materials and methods: We conducted a retrospective cohort study on all the consecutive PAD inpatients in 2008. Data on the patients' demographic characteristics, medical history, treatment, outcome and laboratory tests measurements were retrieved from the medical records. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
2
13
2
Order By: Relevance
“…5,11,12 shown to be associated with a higher risk of mortality and cardiovascular events in patients with peripheral artery disease undergoing revascularization or amputation. 13 Our study strengthens the support for the association of ARF with mortality and cardiovascular events and expands its association to other secondary complications.…”
Section: Discussionsupporting
confidence: 82%
“…5,11,12 shown to be associated with a higher risk of mortality and cardiovascular events in patients with peripheral artery disease undergoing revascularization or amputation. 13 Our study strengthens the support for the association of ARF with mortality and cardiovascular events and expands its association to other secondary complications.…”
Section: Discussionsupporting
confidence: 82%
“…Postoperative acute kidney injury was the most common postoperative complication occurring in almost half of all patients. While our cohort consisted of patients receiving an array of diverse vascular surgical procedures, the prevalence of AKI using consensus criteria in our cohort appears consistent with the reported values in the vascular surgical literature: 12.7% of patients developed AKI after surgical intervention for peripheral arterial disease 11 while 76% of patients developed AKI after ruptured abdominal aortic aneurysmal repair. 14 Postoperative AKI, when defined using the KDIGO consensus criteria, is a common postoperative complication after major inpatient vascular surgery.…”
Section: Discussionsupporting
confidence: 73%
“…7-10 With the emergence of consensus criteria to standardize the definition of this postoperative complication, especially with mild and moderate degrees of AKI, recent studies within the vascular literature have demonstrated that AKI prevalence ranges from 13%-76% and is associated with adverse perioperative outcomes. 11-14 Many of these studies have focused on the prevalence of AKI after a specific procedure using small patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative kidney injury has been found to affect 12.7% of patients undergoing lower limb revascularisation surgery, and only 23.8% of them have a prior history of chronic kidney disease [1]. In addition to chronic kidney failure, patients with peripheral artery disease (PAD) have frequently multiple risk factors for acute kidney injury (AKI) such as smoking, other cardiovascular diseases, diabetes mellitus, and usage of nephrotoxic medication, including painkillers [2,3].…”
Section: Introductionmentioning
confidence: 99%